The association between urinary lead concentration and the likelihood of kidney stones in US adults: a population-based study - Liang, Dan; Liu, Chang; Yang, Mei (Scientific reports, 2025)
The negative effects of lead exposure on human health have attracted widespread attention. Our present study focused on assessing the relationship between urinary lead levels (ULL) and the risk of kidney stones in US adults. We used data from NHANES 2007–2018 for this cross-sectional study, where participants had complete data on ULL and kidney stones. The correlation between ULL and kidney stones was explored by weighted multiple logistic regression analysis. In addition, we also performed subgroup analysis and interaction tests. A total of 8325 subjects were included, and the prevalence of kidney stones was 9.90%. In the fully adjusted model, we observed a positive association between ULL and the risk of kidney stones (OR:1.07, 95% CI: 1.01–1.14, p = 0.03). Participants in the highest quartile of ULL had a 64% higher risk of kidney stones than those in the lowest quartile of ULL (OR:1.64, 95% CI: 1.05–2.57, p = 0.03). Subgroup analysis and interaction test indicated that the association between ULL and the risk of kidney stones was similar in different population settings. The findings of this study indicate a positive correlation between urine lead concentration and the risk of kidney stones. The potential prognostic value of the urine lead concentration for kidney stone outcomes was another new area investigated in this study. However, further prospective clinical trials are needed to confirm the role of urine lead in the pathogenesis of kidney disease and to validate urine lead as a reliable predictor of kidney stone risk.